Water and sediment database for coastal monitoring network in the central Yukon-Kuskokwim Delta, 1994-2023 ... - Jorgenson, Mark Torre (NSF Arctic Data Center, 2025)
The database includes measurements of water quality (depth, pH, EC (electrical conductivity)) and sediment accumulation at 174 stations in the central portion of the Yukon-Kuskokwim Delta from 1994 to 2023. Measurements were made of water depth above or below the ground surface in small wells (PVC plastic pipe, 25 millimeter diameter, 0.3 to 1.0 meter deep) and for electrical conductivity and pH using portable probes (Oakton EC/pH meter). Mean EC values can be calculated by ecotype and geomorphic unit. Surface-accretion (organic matter and mineral sediment) thicknesses were obtained at 93 stations along 11 transects by measuring depth of materials relative to thin paint layers that were sprayed on the surface during various years from 1994 to 2016. The last measurements were made in 2023, a year after ex-Typhoon Merbok became an extratropical storm as it extended into the Bering Sea. ...